RED AF : revealing the true colours of Asian flush - Wong, Dorothy Kang Min (2018)
This paper presents ‘RED AF’, the first health communications campaign in Singapore that seeks to raise awareness of Asian Flush and its associated health implications. It is conceptualised and executed by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Asian Flush, a genetic condition that sharply increases the risk factor of long-term health risks for drinkers, affects approximately one in three Singaporeans. Yet, little local literature and public awareness exists on this health issue. Given the upwards trend of high-risk drinking behaviour among young adults here, the campaign aims to bridge the information gap on Asian Flush, cultivating a safer and healthier drinking culture in Singapore – particularly among university students. Guided by a cogent understanding of the target audience, the campaign worked to improve awareness and beliefs by humanising the health problem through humour and culturally-tailored messages. Prominent creative tactics included the development of an original online interactive game and the adaptation of popular drinking games. The campaign’s significance is most evident in its strong media engagement across 21 channels, earning more than $300,000 in PR value; and the overwhelmingly positive response towards its viral edutainment video. Ultimately, the campaign succeeded in increasing the saliency of Asian Flush and its associated health risks. It also prompted substantial perceptual and behavioural change in its target audience through novel digital initiatives and culturally competent content.